Effect of Quality of Work Life on Job Burnout: A Field Study on a Sample of Female Administrative Employees in the General Department of Education in Riyadh - ALhaddab, Taghreed; ALmekhlafy, Abdulmalik (The Arab Journal of Administration, 2020)
The study aims at identifying the effect of the quality of work life on job burnout for a sample of (390) female administrative employees in the General Department of Education in Riyadh, as well as the substantial differences in the employees’ responses to the quality of work life and job burnout variables, which are attributed to personal and job-related factors. The research findings indicate an average quality of work life in the General Department of Education. Moreover, the Study did not detect any case of job burnout in general, except an average level of emotional exhaustion. Further, the study reveals a substantial effect for the «quality of work life» variable on the job burnout, which interprets (35%) of the variance in the job burnout levels, mainly in the three dimensions (Working conditions, Home-work interface, and General well-being). The study also suggests statistically significant differences in the answers of the respondents to the quality of work life according to the «educational qualification» variable, in favor of employees with educational qualification (High school or below); and according to the «job category» variable, in favor of (Fifth category and less). However, there is no statistical significance for job burnout attributed to personal and job-related factors.